2014
DOI: 10.1590/1413-78522014220400642
|View full text |Cite
|
Sign up to set email alerts
|

Profile of trauma victims of motorcycle accidents treated at hospital São Paulo

Abstract: OBJECTIVE: To evaluate retrospectively, through analysis of medical records, the epidemiological aspects of patients traumatized by motorcycle accidents treated at the orthopedics ward, Hospital São Paulo, Brazil. METHODS: It is a retrospective observational study. The analysis of patients' medical records comprised the period from January 2008 to December 2009. The data checked were: age, gender, type of collision, type and location of fracture, treatment performed (conservative or surgical), type of surgery,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 12 publications
3
16
1
6
Order By: Relevance
“…This result corresponds to what was reported by the teaching hospital [8]. The type of collision was against a vehicle (66.1%), which is greater than what was reported by the hospital [8] (55.2%) and in Sao Paulo Hospital [11] (45.4%).…”
Section: Discussionsupporting
confidence: 84%
“…This result corresponds to what was reported by the teaching hospital [8]. The type of collision was against a vehicle (66.1%), which is greater than what was reported by the hospital [8] (55.2%) and in Sao Paulo Hospital [11] (45.4%).…”
Section: Discussionsupporting
confidence: 84%
“…The prevention of lower limb injuries is more important for developing nations like India for its economy. It has been previously shown that lower limb injuries constitute the majority in trauma and road traffic accidents [3]. Lower limb injury generally involves young and productive people so it is the prime responsibility of the society to prevent such incidents [4][5][6][7].…”
Section: International Journal Of Medical Research and Reviewmentioning
confidence: 99%
“…Nas últimas décadas, no Brasil, houve aumento expressivo do número de acidentes relacionados às ocorrências de trânsito e à utilização de motocicletas [1][2][3][4][5][6] . Dada à natureza do veículo, muitos destes eventos resultam em morte, em ferimentos graves, ou em sequelas permanentes [7][8][9][10] . Os maiores riscos de mortalidade por acidente de motocicleta são de jovens entre 15 e 49 anos implicando em um grande custo social.…”
Section: Introductionunclassified